Talking With Your Child - Kate Fogarty; Evelyn Rooks-Weir; Millie Ferrer-Chancy (EDIS, 2009)
Revised! FCS2006, a 3-page illustrated fact sheet by Kate Fogarty, Evelyn Rooks-Weir, and Millie Ferrer-Chancy, gives parents suggestions of ways to help their children’s language skills develop. Includes references. Published by the UF Department of Family Youth and Community Sciences, November 2009.